Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1002/cncr.11930
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous itraconazole for prophylaxis of systemic fungal infections in patients with acute myelogenous leukemia and high‐risk myelodysplastic syndrome undergoing induction chemotherapy

Abstract: The total syntheses of the structurally unique and moderately cytotoxic pyrrolosesquiterpenoid glaciapyrrol A that has been isolated from a marine streptomycete by Macherla et al.1 and of seven of its stereoisomers have been performed from geraniol or nerol, respectively, using a known diastereoselective Ru‐catalysed approach for the synthesis of tetrahydrofurans previously reported by Stark and co‐workers.5 Comparison of 1H and 13C NMR data unambiguously clarified the relative configuration of natural glaciap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Avoiding the hospitalisation of patients in areas where there is construction and the use of high-efficiency particulate air (HEPA) filtration, with or without laminar air flow ventilation, have both proven useful [174]. A meta-analysis suggested that itraconazole was effective in preventing fungal infections in neutropenic patients [175]. Recent studies confirmed the efficacy of posaconazole as IPA prophylaxis in patients with acute myelogenous leukaemia, myelodysplastic syndrome or HSCT [176][177][178].…”
Section: Treatmentmentioning
confidence: 99%
“…Avoiding the hospitalisation of patients in areas where there is construction and the use of high-efficiency particulate air (HEPA) filtration, with or without laminar air flow ventilation, have both proven useful [174]. A meta-analysis suggested that itraconazole was effective in preventing fungal infections in neutropenic patients [175]. Recent studies confirmed the efficacy of posaconazole as IPA prophylaxis in patients with acute myelogenous leukaemia, myelodysplastic syndrome or HSCT [176][177][178].…”
Section: Treatmentmentioning
confidence: 99%
“…In our recent review of causes of death among patients undergoing induction chemotherapy for acute myelogenous leukemia (AML) or myelodysplastic syndrome (MDS), invasive fungal infection was the most common, and aspergillosis, alone or in combination with bacterial infection, was the most common fungal infection (12).…”
mentioning
confidence: 99%
“…Prophylactic fluconazole has been shown to significantly reduce the number of yeast infections and the need for empirical amphotericin B in such patients (19). Unfortunately, none of the prophylactic antifungal regimens in current use are demonstrably superior for preventing invasive aspergillosis (13)(14)(15), and thus both an effective regimen and a way of identifying patients at particular risk of invasive fungal infection are still needed.…”
mentioning
confidence: 99%
“…124 neutropenic patients were randomized between caspofungin 50 mg/day vs Itra 200 mg/day, at a median of 23 days on the study, both drugs provided comparable antifungal prophylaxis and were well tolerated 58 Caspofungin was equivalent to AmB as a primary treatment of patients with invasive candidiasis and candidemia 86 Interaction: CY m blood-level of caspofungin by 35%, and may induce liver toxicity, in absence of further data such combination is not recommended. Caspofungink tacrolimus level by 20%.…”
Section: Posaconazolementioning
confidence: 99%
“…At a median of 23 days on the study, both drugs provided comparable antifungal prophylaxis and were well tolerated. 58 Unlike the triazoles, caspofungin is neither a substrate nor an inhibitor of the P-450 hepatic cytochrome enzymes system. Preclinical and pharmacokinetic studies have shown an increase in plasma concentration of caspofungin when cyclosporine was administered concomitantly, possibly the result of reversible inhibition of uptake into hepatic tissue.…”
Section: Echinocandinsmentioning
confidence: 99%